On Frankincense-scented Soaps, Peelings and Cleansers or on Cosmetics and Commotics in Antiquity and Early Byzantium - Maciej Kokoszko; Zofia Rzeźnicka (Vox Patrum, 2021)
Cosmetology (τέχνη κοσμητική), i.e. a resource of means aimed at maintaining natural beauty of a human, was not frowned upon by the pagans nor by the Christians. What they disapproved of was commotic (κομμωτικὴ τέχνη), defined (by Galen, Clement of Alexandria, Gregory of Nyssa and Theodoret of Cyrus ) as an art of changing the outward appearance to the detriment of nature and one’s health.  The present study has been designed to discuss select information, extant in Book VIII of Iatricorum libri by Aëtius of Amida, on what preparations were at disposal of the people of the Mediterranean who cared for their physical cleanliness (as well as health), regardless of their religious proclivities. It is focused on a number of prescriptions for face and body cleansers, though the analysed inventory has been limited to the ones including frankincense. The research material has turned out to be ample enough to draw conclusions on the ingredients used in such agents, their effectiveness, the form of the preparations, their application mode as well as on the addressees of the recipes. It has been also suggested that the formulas were compiled from the body of medical knowledge akin to what was collected by Titus Statilius Crito in his work On cosmetics.